2020
DOI: 10.1371/journal.pone.0237713
|View full text |Cite
|
Sign up to set email alerts
|

Isn’t high school bad enough already? Rates of gender harassment and institutional betrayal in high school and their association with trauma-related symptoms

Abstract: Germinal studies have described the prevalence of sex-based harassment in high schools and its associations with adverse outcomes in adolescents. Studies have focused on students, with little attention given to the actions of high schools themselves. Though journalists responded to the #MeToo movement by reporting on schools’ betrayal of students who report misconduct, this topic remains understudied by researchers. Gender harassment is characterized by sexist remarks, sexually crude or offensive behavior, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Our second hypothesis was supported. Similar to prior research on institutional betrayal in different contexts [ 4 , 7 , 11 ], we found that experiences of institutional betrayal are associated with symptoms of general trauma symptoms (e.g., depression, anxiety, sleep problems). We also found that experiences of institutional betrayal are associated with COVID-19-specific intrusion and avoidance cognitions (e.g., intrusive thoughts about COVID-19, spending a lot of time trying to avoid thinking about COVID-19).…”
Section: Study 1 Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our second hypothesis was supported. Similar to prior research on institutional betrayal in different contexts [ 4 , 7 , 11 ], we found that experiences of institutional betrayal are associated with symptoms of general trauma symptoms (e.g., depression, anxiety, sleep problems). We also found that experiences of institutional betrayal are associated with COVID-19-specific intrusion and avoidance cognitions (e.g., intrusive thoughts about COVID-19, spending a lot of time trying to avoid thinking about COVID-19).…”
Section: Study 1 Discussionsupporting
confidence: 88%
“…The relationships between COVID-19-related institutional betrayal, current trauma symptoms, and COVID-19-specific cognitions persisted, even when controlling for gender and familiarity with someone infected with COVID-19. Similar unique associations between institutional betrayal and symptoms of distress have been replicated in numerous other studies [ 4 , 11 , 12 ].…”
Section: Study 1 Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, since we assessed non-traumatic events only, the severity of the events may also largely differ among each person. Recent studies reported that PTSD-like symptoms were observed in people distressed by interpersonal problems including various kinds of harassment (e.g., power and sexual harassment at school [ 40 ] and the workplace [ 41 ]) and school bullying issues among children [ 42 ]. Even if these stressful events do not objectively meet the traumatic ones required for diagnosing PTSD, these stressful events and the related distressed conditions are serious.…”
Section: Discussionmentioning
confidence: 99%
“…The Institutional Betrayal Questionnaire (IBQ) was first developed to measure institutional betrayal in individuals who have experienced sexual assault [4]. Since then, the scale has been adapted to assess institutional betrayal in additional settings: IBQ-Health measures institutional betrayal in healthcare systems, IBQ-Climate measures institutional betrayal in school settings, and IBQ-Covid measures experiences regarding institutional protocols and policies regarding COVID-19 [12][13][14]. There is currently no appropriate scale to assess feelings of betrayal, humiliation, or embitterment in the first responder population.…”
Section: Introductionmentioning
confidence: 99%